Presenting a Coherent Model of Augmented Reality Marketing in Advertising Based on the Meta-Synthesis Approach - Shakeri, Majid; Rashidi, Ehtsham; Vakil Alroaia, Younes (Business, Marketing, and Finance Open, 2025)
Augmented reality marketing refers to the use of augmented reality in marketing to enhance customer experiences. Augmented reality (AR) has increasingly attracted the attention of both managers and researchers in recent years. AR is a potential technology that enriches consumer experiences and transforms marketing. The purpose of this study is to present a coherent model of augmented reality marketing in advertising based on a meta-synthesis approach. To this end, using a mixed-method research approach and the meta-synthesis tool—which includes the seven-step method of Sandelowski and Barroso (2006)—a systematic evaluation and analysis of the results and findings of prior studies was conducted, ultimately reviewing 43 articles. In the quantitative phase, the Shannon entropy method was used to prioritize the components of the identified themes. Augmented reality was classified into three dimensions: AR characteristics, purchase intention, and subjective norms. The characteristics of AR included the AR mirror, perceived usefulness, emerging brands, and digital transformation; purchase intention included informativeness, usefulness, simplification, and persuasion; and subjective norms included AR acceptance, aesthetics, consumer connection experience, and perceived enjoyment. In total, the contribution of AR characteristics (15%), purchase intention (58%), and subjective norms (27%) to augmented reality marketing was determined. The meta-analysis of this study provides insight into the need to utilize augmented reality in marketing, which proves beneficial for developing marketing strategies.